2000
DOI: 10.1103/physrevlett.84.2726
|View full text |Cite
|
Sign up to set email alerts
|

Peres-Horodecki Separability Criterion for Continuous Variable Systems

Abstract: The Peres-Horodecki criterion of positivity under partial transpose is studied in the context of separability of bipartite continuous variable states. The partial transpose operation admits, in the continuous case, a geometric interpretation as mirror reflection in phase space. This recognition leads to uncertainty principles, stronger than the traditional ones, to be obeyed by all separable states. For all bipartite Gaussian states, the Peres-Horodecki criterion turns out to be necessary and sufficient condit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
2,539
0
33

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,082 publications
(2,597 citation statements)
references
References 17 publications
25
2,539
0
33
Order By: Relevance
“…Any two-mode state can be fully described by a covariance matrix (assuming for simplicity that its mean value is 0), which in standard form [21,22] is written as…”
Section: Gaussian Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Any two-mode state can be fully described by a covariance matrix (assuming for simplicity that its mean value is 0), which in standard form [21,22] is written as…”
Section: Gaussian Statesmentioning
confidence: 99%
“…By applying S 2 (r) to a couple of vacuums, we obtain a pure state called the two-mode squeezed vacuum, with a = b = [15]. The necessary and sufficient separability criterion for a two-mode Gaussian state σ has been shown to be the positivity of the partial transposed stateσ [21][22][23]. This is equivalent to checking the conditionν − 1 [10], whereν − is the lowest symplectic eigenvalue ofσ .…”
Section: Gaussian Statesmentioning
confidence: 99%
“…Since we are working with Gaussian states, there are necessary and sufficient criterion to determine if the state is entangled [16][17][18]. Simon [16] has shown that for any two-mode Gaussian state, if the following inequality is observed…”
Section: General Properties Of Two-mode Gaussian Statesmentioning
confidence: 99%
“…As far as I know no experiment has yet been performed along this line on single photons, but those experimentalists who pioneered the field of quantum optics could have made it in passing. Kimble has been prolific in squeezed and other quantum states in cavity using the technique of parametric down-conversion and the demonstration by his group (Ou et al 1992a, b) realizing the EPR paradox for continuous variables using these techniques inspired and paved way for the later establishment of a theory for model-independent continuous-variable entanglements (Duan et al 2000;Simon, 2000). The group has demonstrated how entangled photons may be created and are not separable.…”
Section: Future Experimentsmentioning
confidence: 99%
“…For example, a two-particle system is assumed to be characterized by a difference of x coordinates, x 1 -x 2 , and the sum of the x-components of their momenta, p 1x + p 2x , which is fully consistent with the QM formalism as follows from the commutativity between x 1 -x 2 and p 1x + p 2x . The first experimental demonstration of the physics of EPR was made by Kimble's group (Ou et al 1992a, b), which later led to theoretical criteria for unambiguous verification of true entanglement (Duan et al 2000;Simon, 2000).…”
mentioning
confidence: 99%